ETIKA KOMUNIKASI DI MEDIA SOSIAL: KAJIAN AL-QURAN SURAT AN-NUR AYAT 11-15 - Aisyah, Nur; Nasution, Hasyimsah (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
The contemporary world is vastly different from the past, particularly in the realm of communication and information. Modern advancements have facilitated seamless global communication, effectively shrinking the vast world. The internet, as a new communication medium, has had both beneficial and detrimental impacts on society. This study aims to explore the interpretation of Surah An-Nur 24:11-15, the communication ethics contained within these verses, and their application in social media interactions. Employing a qualitative library research method, data was gathered through an extensive review of relevant literature, with the Qur’an as the primary source. The communication ethics in Surah An-Nur 24:11-15 are encapsulated in three principal values: (1) speaking kindly, (2) honesty, and (3) accuracy of information (tabayyun). These ethical values are crucial for fostering peaceful and harmonious social interactions. This study highlights that these principles serve as essential guidelines for social media users, advocating for responsible and wise usage. By adhering to these values, individuals can enhance their social media interactions in accordance with Islamic teachings. The study underscores the importance of understanding and applying Islamic ethics in social media usage. Consequently, it is recommended that insights from this research be further developed and used as a reference to examine social media communication ethics from an Islamic perspective, employing diverse methodological approaches